Komparasi hasil belajar menggunakan video berbasis CTL dan PPT di SMA Adabiah pada materi hukum newton tentang gerak dan gravitasi - Annisa Fitri; Murtiani Murtiani; Desnita Desnita; Asrizal Asrizal (Universitas Negeri Padang, 2020)
This study aims to find student learning outcomes using CTL and PPT-based videos for 10th grade students at Adabiah Padang High School on Newton's law material about motion and interaction. This type of research is an experiment with a randomized control group design only. This study involved two experimental classes, the first class using CTL-based videos and the second class using PPT. This study discusses aspects of attitude, knowledge and skills. Assessment is based on the instrument. Based on the results of data analysis that can prove student learning outcomes on aspects of attitudes, knowledge and skills of CTL-based videos are higher than the PPT class, the average results of CTL-based video student grade grades are higher than the PPT class, and related to student learning outcomes with applying CTL-based videos and applying PPT to Newton's law material about motion and applying at Adabiah High School Padang with a 95% confidence level